2020
DOI: 10.2196/18309
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Internet Health Information–Seeking Behaviors Among Young Adults Living With HIV Across the United States: Longitudinal Observational Study

Abstract: Background Consistent with young adults’ penchant for digital communication, young adults living with HIV use digital communication media to seek out health information. Understanding the types of health information sought online and the characteristics of these information-seeking young adults is vital when designing digital health interventions for them. Objective This study aims to describe characteristics of young adults living with HIV who seek hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Li et al reported that a higher level of education, female sex, and a younger age were associated with higher odds of seeking information online [ 18 ]. Invariably, other studies reported that a lower level of education was associated with a lower likelihood of HIT use in the form of looking up health information [ 19 , 20 ]. These findings may be related to the effect of health literacy on the use of technological tools.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that a higher level of education, female sex, and a younger age were associated with higher odds of seeking information online [ 18 ]. Invariably, other studies reported that a lower level of education was associated with a lower likelihood of HIT use in the form of looking up health information [ 19 , 20 ]. These findings may be related to the effect of health literacy on the use of technological tools.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of patients empowered them to understand the value of the system and to provide their views and needs, thus facilitating the development of a user-adapted platform. Furthermore, the need has been emphasized for developers of digital health information to use numerous innovative strategies to meet both the needs and expectations of targeted audiences [ 46 ]. During consultative meetings in the early phases of our project, village leaders indicated the need to use the platform to disseminate news and information to villagers.…”
Section: Discussionmentioning
confidence: 99%
“…As an early example of librarians working to provide LGBTQ+ health information, some librarians created print reference materials to link consumers to community resources for HIV/AIDS, providing pre-internet access to information when reliable information was not always easy to access or identify [21][22][23][24]. Recent studies have focused on health information seeking by sexual and gender minority youth and information seeking by men who have sex with men (MSM) on topics such as pre-exposure prophylaxis (PrEP), a medication that decreases the risk of HIV transmission [25,26,27]. Other studies have focused on information seeking by transgender and gender diverse persons, in areas such as breast cancer screening and human papillomavirus vaccination [28,29].…”
Section: Introductionmentioning
confidence: 99%